2010
DOI: 10.1002/ajmg.b.31012
|View full text |Cite
|
Sign up to set email alerts
|

Association studies of −3081(A/T) polymorphism of norepinephrine transporter gene with attention deficit/hyperactivity disorder in Korean population

Abstract: Recent studies showing the improvement of ADHD symptoms obtained with the highly selective noradrenergic reuptake inhibitor, atomoxetine, demonstrate that the noradrenergic system plays the role of pathophysiology in this disorder. It is revealed that the norepinephrine transporter gene (SLC6A2) is a possible candidate gene directly related to ADHD. To determine possible roles of the SLC6A2 as a susceptibility gene for ADHD, we performed the genetic association study for a functional À3081(A/T) polymorphism, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…This SNP was shown to downregulate the expression of SLC6A2 significantly, representing a very interesting candidate for molecular genetic studies in ADHD. In contrast to the results reported by Kim et al (2006) and Joung et al (2010) and in line with the findings of Cho et al (2008), we did not detect significant transmission disequilibrium for the T-allele in our sample (Kim et al 2006;Joung et al 2010;Cho et al 2008). Our study is based on family data and provides robust results against stratification admixture in contrast to case-control studies.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…This SNP was shown to downregulate the expression of SLC6A2 significantly, representing a very interesting candidate for molecular genetic studies in ADHD. In contrast to the results reported by Kim et al (2006) and Joung et al (2010) and in line with the findings of Cho et al (2008), we did not detect significant transmission disequilibrium for the T-allele in our sample (Kim et al 2006;Joung et al 2010;Cho et al 2008). Our study is based on family data and provides robust results against stratification admixture in contrast to case-control studies.…”
Section: Discussionsupporting
confidence: 69%
“…Though Kim et al (2008) further underlined the importance of SLC6A2 in ADHD by an extended association study, the T-3081A variant was not included in the set of investigated variants. In a recent combined case-control and family-based study on Korean children affected by ADHD, Cho et al (2008) were not able to confirm the association for the T-3081A SNP, while Joung et al reported association in a further Korean sample with relatively high odds ratios (Cho et al 2008;Joung et al 2010).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The human NET gene [solute carrier family 6 (neurotransmitter transporter), member 2 (norepinephrine transporter; SLC6A2)] maps to chromosome 16 (16q12.2) and consists of 16 exons (Porzgen et al, 1995), encoding for a protein of 617 amino-acids (Gelernter et al, 1993). So far, reports on potential associations between specific single nucleotide polymorphisms (SNPs) of the NET gene and ADHD or related phenotypes have been controversial (Barr et al, 2002;Bobb et al, 2005;Brookes et al, 2006;Cho et al, 2008;Joung et al, 2010;Kim et al, 2006Kim et al, , 2008bMcEvoy et al, 2002;Renner et al, 2011;Xu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%